2022
DOI: 10.1111/cts.13385
|View full text |Cite
|
Sign up to set email alerts
|

The vaccine hesitancy continuum among hesitant adopters of the COVID‐19 vaccine

Abstract: Vaccination is a strategy for mitigating the impact of coronavirus disease 2019 (COVID-19) at both the individual and population levels. Vaccine hesitancy is identified as a significant threat to global health by the World Health Organization (WHO). Vaccine hesitancy has been theorized as a continuum encompassing a range of attitudes, beliefs, emotional orientations, ideologies, and health-seeking behaviors. Individuals who received the COVID-19 vaccine but also indicated some level of hesitancy about vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Our findings align with prior research that has investigated differences in perspectives along the continuum of vaccine hesitancy among adults in the United States with varying degrees of hesitancy toward or refusal of COVID-19 vaccines. 18 , 19 Participants in our study reflected on how their experiences with Long COVID impacted their perceptions about COVID-19 vaccines, including individuals who were convinced to receive, or considered receiving, a COVID-19 vaccine for the first time due to their Long COVID experience, as well as individuals who received an initial COVID-19 vaccine, but were uncertain about receiving future booster doses due to the potential impact on their Long COVID symptoms. These findings demonstrate that the unique perspectives of Long COVID patients should be considered when discussing vaccination recommendations with this population.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings align with prior research that has investigated differences in perspectives along the continuum of vaccine hesitancy among adults in the United States with varying degrees of hesitancy toward or refusal of COVID-19 vaccines. 18 , 19 Participants in our study reflected on how their experiences with Long COVID impacted their perceptions about COVID-19 vaccines, including individuals who were convinced to receive, or considered receiving, a COVID-19 vaccine for the first time due to their Long COVID experience, as well as individuals who received an initial COVID-19 vaccine, but were uncertain about receiving future booster doses due to the potential impact on their Long COVID symptoms. These findings demonstrate that the unique perspectives of Long COVID patients should be considered when discussing vaccination recommendations with this population.…”
Section: Discussionmentioning
confidence: 99%
“…The first theme confirmed that hesitation about COVID-19 vaccination has various roots, spanning from health denialism through the fear of side effects to a libertarian outlook [ 27 ]. There is a growing corpus of scientific literature on denialism and vaccine hesitancy; however, more authors are interested in the determinants of refusal or hesitation to get vaccinated than in the motivation of those who have accepted vaccination [ 27 , 28 , 29 , 30 , 31 , 32 ]. Our study showed that apart from those who were simply afraid of COVID-19 infection and its consequences, several interviewees treated vaccination as their obligation.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, we observed some propensity toward conspiracy beliefs, especially associated with vaccination. We had also previously marked a high prevalence of conspiracy beliefs regarding COVID-19 in Polish society [ 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of vaccine hesitancy published in highly reputable medical journals have conflated vaccination status and the attitude of hesitancy [13] . Emerging research demonstrates individuals who have been vaccinated commonly report some degree of vaccine hesitancy either months before receiving the vaccine, or even the same day as having received it [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . Therefore, this study distinguishes vaccine hesitancy (an attitude) from vaccination status (a behavior) [22] and recognizes individuals who are “hesitant adopters” (i.e., individuals who were both hesitant and vaccinated).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research on hesitant adopters has focused on small samples [ 21 , 23 ], qualitative analysis [24] , and single state geographic samples [19] . Given the past research demonstrating how common vaccine hesitancy is among the vaccinated [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , it is important to consider the presence of vaccine hesitancy and its correlates even among individuals who have received a dose of COVID-19 vaccine. To our knowledge, there are no studies examining hesitancy among vaccinated individuals in a diverse sample of US adults.…”
Section: Introductionmentioning
confidence: 99%